Power and efficiency analysis of high-frequency Wireless Power Transfer Systems. (January 2017) - Di Capua, Giulia; Femia, Nicola; Petrone, Giovanni; Lisi, Gianpaolo; Du, Dingkun; Subramonian, Rajaram
Highlights: An enhanced model for loss analysis of low-power high-frequency Wireless Power Transfer Systems (WPTSs) is proposed. Switching losses of semiconductor devices and modulation of duty-cycle and phase of secondary side rectifier are included. Experimental measurements on a 2W@6.78 MHz WPTS demonstrate the validity of the analysis. Identification of optimal design solutions in the choice of the WPTS elements - including power MOSFETs and operating conditions – can be achieved. Abstract: This paper discusses the losses analysis of low power high-frequency Wireless Power Transfer Systems (WPTSs). Ideal models for efficiency evaluation of WPTS can predict performances that are quite far from the real ones. The model proposed in this paper includes semiconductor devices losses, as well as modulation of duty-cycle and phase for the secondary side rectifier. The global influence of semiconductor devices and control parameters on the overall WPTS performances is numerically determined by solving the herein discussed non linear equations system. Experimental measurements realized on a 2 W@6.78 MHz WPTS demonstrate the validity of this analysis.